Moderate Effects of Low-Intensity Behavioral Intervention. Issue 1 (January 2020) - Lotfizadeh, Amin D.; Kazemi, Ellie; Pompa-Craven, Paula; Eldevik, Sigmund
We compared clinical outcomes in a treatment group of 98 individuals who received between 8 and 15 weekly hours ( M = 10.6; SD = 1.7) of applied behavior analysis (ABA) intervention with a comparison group of 73 individuals who received another provision, including some ABA, (between 1.4-8 weekly hours, M = 5.7; SD = 1.6). After 2 years, the treatment group made greater gains than the comparison group on language and social skills, and other areas assessed by the Verbal Behavior Milestones Assessment and Placement Program (VB-MAPP). We evaluated the outcome on adaptive skills for a smaller sample of participants using the Vineland Adaptive Behavior Scales II (VABS), but found no significant differences between the treatment ( n = 17) and comparison groups ( n = 11). Although the treatment group made important and clinically meaningful gains, the gains were moderate. These findings underline the importance of intervention intensity and provide further support for a dose–response relationship between ABA intervention hours and outcomes.